A Transcriptomic Dataset of Liver Tissues from Global and Liver-Specific Bmal1 Knockout Mice - Guohao Han; Dan Li; Haisen Zhang; Chao Li; Luda Yang; Tiantian Ma; Xuerong Wang; Bairong Ma; Xiaodie Wu; Yang Tao; Ziang Wang; Aihua Wang; et al. (Scientific Data)
Abstract The circadian clock regulates various physiological processes in mammals. The core circadian clock gene Bmal1 is crucial for maintaining the oscillations of the circadian clock system by controlling the rhythmic expression of numerous circadian clock-controlled genes. To explore the transcriptional changes associated with Bmal1 deletion in liver tissues, we collected liver tissues from global and liver-specific Bmal1 knockout mice, along with their respective control groups, at two circadian time points (CT2 and CT14) and used them for transcriptome sequencing analysis. Genotyping, locomotor activity analysis, and comprehensive quality control analyses, including base quality scores, GC content, and mapping rates, confirmed the high quality of sequencing data. Differential expression analysis and RT-qPCR validation confirmed the reliability and validity of the dataset. These data offer a valuable resource for researchers investigating the role of BMAL1 in liver physiology, pathology, and the broader field of circadian biology.